(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The present study was undertaken to know the effect of micronutrient, seriboost on mulberry and cocoon characters of silkworm, Bombyx mori L. The mulberry leaves were sprayed with seriboost in different concentrations (2%,5% and 10%) and feeding them to the silkworms. Among these three concentrations tested, it was observed that the 5% registered higher yield parameters in mulberry and cocoon characters in B.mori followed by 10% , 2% and control batches.